2005
DOI: 10.1197/j.aem.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Perceived Health Consequences of Hunger in Emergency Department Patient Populations

Abstract: Objectives: Hunger is associated with chronic poor health and may force patients to make choices that acutely impact their health. This study was conducted to determine the prevalence of hunger, some of the choices it forces, and its perceived health effects among emergency department (ED) patients. Methods: A validated survey about hunger, choosing between food and medicine, and perceived adverse health outcomes was administered in English, Spanish, and Somali to non-critically ill ED patients or their parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Of primary interest was the extent to which families exchange scarce resources to meet these needs and enhance their overall well‐being. Consistent with convenience sample‐based studies that asked people whether they had found themselves faced with the choice of seeking medical care and purchasing food (e.g., Biros et al., 2005; Kersey et al., 1999; Nelson et al., 1998), the results indicated that expenditures on one basic need (medical care) reduced the resources available to support consumption of another basic need (food). Counter to Biros et al.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Of primary interest was the extent to which families exchange scarce resources to meet these needs and enhance their overall well‐being. Consistent with convenience sample‐based studies that asked people whether they had found themselves faced with the choice of seeking medical care and purchasing food (e.g., Biros et al., 2005; Kersey et al., 1999; Nelson et al., 1998), the results indicated that expenditures on one basic need (medical care) reduced the resources available to support consumption of another basic need (food). Counter to Biros et al.…”
Section: Discussionsupporting
confidence: 67%
“…Relative to the literature on food insecurity and medical expenditure, little is known about families' efforts to coordinate food and medical care spending. Biros et al (2005) examined data from 930 adult emergency department patients and found that 18% made explicit choices between food and medicine, including delaying the purchase of medicine to buy food or trading off between food and medicine purchases. Earlier, Kersey et al (1999) investigated hunger among 297 patients from the same hospital and reached similar conclusions.…”
Section: Relationship Between Food and Medical Expendituresmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia may result from the inability to afford diabetes-appropriate foods, overconsumption during food adequacy (a behavior often observed among adults exposed to episodic food scarcity), reduced medication adherence, or lack of medication intensification by clinicians because of frequent hypoglycemic episodes or unpredictable dietary intake 6,14. Food-insecure patients are also more likely to have to choose between food and diabetes medication or supplies, a choice that is also likely to predispose patients to either hypoglycemia (if medications are taken instead of food) or hyperglycemia (if food is eaten instead of medications) 15,16. Our findings confirm the clinical impact of these difficult budget decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Lower quality diets and reduced intake of nutrients among members of food-insecure households (Bhattacharya et al, 2004;Dixon et al, 2001;Rose and Oliveira, 1997) may contribute to the poorer health and increased morbidity and mortality that have been associated with food insecurity (Siefert et al, 2004;Stuff et al, 2004;Vozoris and Tarasuk, 2003). The health effects associated with food insecurity may be even more detrimental for adults with disabling or chronic health conditions (Biros et al, 2005;Nelson et al, 1998;Nelson et al, 2001;Seligman et al, 2010;Seligman et al, 2012). Nutrition and human service agencies that are focused on the population of persons with disabilities and those with chronic disease recognize the importance of proper nutrition in treating chronic conditions (Association of Nutrition Service Agencies, 2006;New York State Department of Health, 2003;Wallace et al, 2007).…”
Section: Food Insecurity and Disability Introduction And Motivationmentioning
confidence: 99%